PaleobioDB: an R package for downloading, visualizing and processing data from the Paleobiology Database. Issue 4 (2nd December 2014) - Varela, Sara; González‐Hernández, Javier; Sgarbi, Luciano F.; Marshall, Charles; Uhen, Mark D.; Peters, Shanan; McClennen, Michael
<x xml:space="preserve">Abstract</x> The fossil record acts as a time machine, providing data on the morphology, ecology and biogeography of ancient species. Therefore, ideally, fossil data should be included in evolutionary, macroecological and biogeographical studies. However, paleontological data are often not used in biological research, in part because of the difficulty of extracting occurrence records from the primary literature. The goal of the Paleobiology Database is to make these records generally accessible, but unlike databases such as Genbank and GBIF, a ready‐made interface to the R computing environment has not been available. We have developed paleobioDB, an R package designed to perform easy and flexible queries of the Paleobiology Database, including visualization, downloading and processing of selected data. This package facilitates access to paleontological data in a way that should allow further analysis using other packages and libraries available in R. The paleobioDB package should facilitate the integration of paleontological and neontological datasets, so that data from the deep past can be used to help inform our understanding of living biota, and vice versa.